Breaking the Silence: Addressing Men’s Underrepresentation in Sexual Assault Cases and Policy as a Gender Equality Issue - Oteniya, Samson (feminists@law, 2026)
Male survivors of sexual assault remain significantly underrepresented in the United Kingdom’s (UK) policy, support, and legal frameworks. This policy report identifies this underrepresentation not merely as a gap in crime reporting but as a critical issue of substantive gender equality. Drawing on Fredman’s theory of substantive equality and Connell’s concept of hegemonic masculinity, this report examines how legal definitions, cultural stigma, and gender norms have systematically silenced male victims, thereby contributing to their underrepresentation in sexual assault cases and policy. While awareness has grown in recent years, spurred by high-profile cases and survivor advocacy, many men still encounter persistent barriers to speaking out as victims of sexual assault and accessing justice. The reasons for their silence may lie in deeply rooted societal expectations of masculinity, gender-biased legal classifications, inadequately tailored support services, and exclusion from mainstream gender violence policies. Overcoming these barriers is essential—not only to ensure justice and care for all survivors but as a necessary step toward meaningful gender inclusion.